Pengaruh Promosi Social Media dan Harga Terhadap Minat Beli Konsumen Kripik Singkong G-3 - Fahmi, Moh. Imam (PERFORMA, 2023)
The research which entitled "The Effect of Social Media Promotion and Price on Purchase Intention of Kripik Singkong G-3 Consumers". This research has two objectives, that is,: (1) to know the effect of social media promotion on purchase intention of kripik singkong G-3 consumers (2) To know the effect of price on purchase intention of kripik singkong G-3 consumers. G-3 is a business that runs in snack field that is processed traditionally. Sale that is done by G-3, that is, online and store at small shops. This research uses quantitative method. The population in this research is all potential consumers who use social media (Facebook and Instagram). The sample in this research, that is, 120 respondents. Data collect on us questionnaire that is distributed online. Data process in this research uses multiple linear regression analysis by using SPSS as helping tool in processing data. The results of this research are: (1) Social media promotion affects positive and significant on purchase intention of kripik singkong G-3 consumers. (2) Price affects positive and significant on purchase intention of kripik singkong G-3 consumers. Keywords: social media promotion, price, purchase intention.